2022
DOI: 10.1371/journal.pgph.0000249
|View full text |Cite
|
Sign up to set email alerts
|

Understanding reasons for suboptimal tuberculosis screening in a low-resource setting: A mixed-methods study in the Kingdom of Lesotho

Abstract: Lesotho has one of the highest tuberculosis (TB) incidence rates in the world, estimated at 654/100,000 population. However, TB detection remains low, with only 51% of people with TB being diagnosed and treated. The aim of this study was to evaluate implementation of TB screening and identify drivers of suboptimal TB screening in Lesotho. We used a convergent mixed methods study design. We collected data on the number of health facility visits and the number of clients screened for TB during March-August, 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Although in our setting, the greatest loss from the care cascade was at the initial step of screening people for tuberculosis symptoms [ 10 ], lack of decentralization of laboratory services at the health center was also a major contributor to low tuberculosis detection. Moreover, we found that patients may fail to complete their treatment successfully due to poverty and socioeconomic factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although in our setting, the greatest loss from the care cascade was at the initial step of screening people for tuberculosis symptoms [ 10 ], lack of decentralization of laboratory services at the health center was also a major contributor to low tuberculosis detection. Moreover, we found that patients may fail to complete their treatment successfully due to poverty and socioeconomic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative and quantitative data were analyzed separately, and findings were then integrated for a deeper understanding of the barriers to completing the tuberculosis care cascade. A previous publication reported reasons for suboptimal tuberculosis screening–the first step of the care cascade [ 10 ]. This publication focuses on barriers to completing subsequent steps.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation of systematic screening of TB in high-burden countries is influenced by multiple factors, including low screening and testing capacity, limited understanding of systematic screening techniques, and limited health workers’ competence in TB screening. 19 24 The characteristics of technological innovations and advancements, access, sensitivity, and specificity of chest X-ray techniques facilitate, while cost and providers’ lack of technical competency hinder, the adoption of chest X-rays in systematic TB screening. 25 29 …”
Section: Introductionmentioning
confidence: 99%